2002
DOI: 10.1073/pnas.112336399
|View full text |Cite
|
Sign up to set email alerts
|

Folate deficiency disturbs hepatic methionine metabolism and promotes liver injury in the ethanol-fed micropig

Abstract: Alcoholic liver disease is associated with abnormal hepatic methionine metabolism and folate deficiency. Because folate is integral to the methionine cycle, its deficiency could promote alcoholic liver disease by enhancing ethanol-induced perturbations of hepatic methionine metabolism and DNA damage. We grouped 24 juvenile micropigs to receive folate-sufficient (FS) or folate-depleted (FD) diets or the same diets containing 40% of energy as ethanol (FSE and FDE) for 14 wk, and the significance of differences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
179
4
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 183 publications
(204 citation statements)
references
References 63 publications
18
179
4
1
Order By: Relevance
“…Abnormal hepatic methionine metabolism is an acquired metabolic abnormality in ALD. Previous studies, including ours, reported that chronic alcohol in experimental animals not only caused SAM deficiency, but also elevation of SAH [3,12,13]. These observations are consistent with the study by Lieber et al showing that alcohol consumption decreased hepatic phosphatidylethanolamine N-methyltransferase activity in a baboon model of alcohol-induced hepatic fibrosis [14].…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Abnormal hepatic methionine metabolism is an acquired metabolic abnormality in ALD. Previous studies, including ours, reported that chronic alcohol in experimental animals not only caused SAM deficiency, but also elevation of SAH [3,12,13]. These observations are consistent with the study by Lieber et al showing that alcohol consumption decreased hepatic phosphatidylethanolamine N-methyltransferase activity in a baboon model of alcohol-induced hepatic fibrosis [14].…”
Section: Introductionsupporting
confidence: 92%
“…Decreased hepatic SAM and increased homocysteine levels in ALD have been extensively reported. In addition to its effects on SAM and homocysteine levels, chronic alcohol consumption results in a significant increase in hepatic SAH levels [3,12,13]. Importantly, we showed that accumulation of intracellular SAH sensitized hepatocytes to TNF induced cytotoxicity in vitro, which we postulate is a clinically relevant metabolic alteration in the pathogenesis of ALD [12].…”
Section: Discussionmentioning
confidence: 62%
“…As previously described, 15 24 juvenile Yucatan micropigs were obtained from Sinclair Farms (Columbia, MO) and were pair-fed diets that provided 90 kcal/kg body weight with 15% of kcal as vitamin-free casein, 30% of kcal as corn oil, and 55% of kcal as carbohydrate (control) or diets in which carbohydrate was reduced to 15% and ethanol was substituted to provide 40% of kcal. Folic acid was absent or was added to diets at 14.5 g/kg body Arrows indicate the directions of change in methionine metabolites in response to the diets as previously described.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…[3][4][5][6][7]16 We developed a micropig model for alcoholic liver disease based on 14 weeks of feeding diets that either contained ethanol or were deficient in folate, or both factors in combination. 15 Compared with the control group fed a folate-sufficient diet without ethanol, each folate-deficient diet reduced liver folate by one half, and the combined diet resulted in a fourfold elevation in plasma homocysteine. Ethanol feeding alone increased liver homocysteine levels by one half and reduced liver SAM by one third and the GSH/ oxidized glutathione (GSSG) ratio by one half.…”
mentioning
confidence: 99%
See 1 more Smart Citation